Applying the Theory of Reasoned Action to the Analysis of Juvenile delinquency - Anak Jinang, Grace (PPSP, Universiti Sains Malaysia, 2007)
In order to enhance our understanding of the heterogeneity in adolescents exhibiting disruptive behaviour problems, this research provides an overview of the analysis of juveniles' delinquent behaviours by applying The Theory of Reasoned Action (Fishbein & Ajzen, 1980). This study examines the juveniles' attitude towards delinquenct acts, peers belief and family belief on juveniles' delinquent acts and the intention of juveniles to be involved in delinquent deeds in conjunction with their delinquent behaviours. Using a sample of 171 female juveniles from Sekolah Tunas Bakti Sungai Lereh Melaka, the current study examined the interaction between the juveniles' attitude towards delinquenct acts, peers belief and family belief on juvenile' delinquent acts and the intention of juveniles to be involved in delinquent deeds. The data were coded and analyzed by using SPSS Version 12 involving the usage of two statistical analyses, which are Spearman's Rank Order Correlation (rho) analysis and Mann-Whitney U Test. The result of the analysis shows that the juveniles' attitude towards delinquent acts, peers belief and family belief on juveniles' delinquent acts and the intention of juveniles to be involved in delinquent deeds were associated with delinquent behaviours. There was a significant correlation between the juveniles' attitude towards delinquent acts, peers belief and family belief on juveniles' delinquent acts, the intention of juveniles to be involved in delinquent deeds, and juveniles' delinquent behaviours. There were significant differences in the peers belief and family belief on juveniles' delinquent acts between the age of the juveniles. Findings from the present study indicated that the influence of the peers belief and family belief that influence the juveniles to commit delinquent acts was higher in late adolescence. The results of the study are discussed based on the Theory of Reasoned Action.